High immune cytolytic activity in tumor‐free tongue tissue confers better prognosis in patients with squamous cell carcinoma of the oral tongue. (19th July 2019) - Gu, Xiaolian; Boldrup, Linda; Coates, Philip J; Fahraeus, Robin; Wang, Lixiao; Wilms, Torben; Norberg‐Spaak, Lena; Sgaramella, Nicola; Nylander, Karin
Abstract: Immune cells and cytolytic activity within the tumor microenvironment are being intensively studied. Through transcriptome profiling, immune cell enumeration using the xCell tool and cytolytic activity quantification according to granzyme A ( GZMA ) and perforin ( PRF1 ) mRNA levels, we investigated immunoreactivity in tumor and/or tumor‐free tongue tissue samples from 31 patients with squamous cell carcinoma of the oral tongue and 14 healthy individuals (control tongue tissues). We found significantly altered immune cell compositions ( p  < 0.001) and elevated cytolytic activity ( p  < 0.001) in tumor compared to tumor‐free samples, and altered infiltration of a subset of immune cells (e.g. CD8 + T cells, p  < 0.01) as well as increased cytolytic activity ( p  < 0.001) in tumor‐free compared to control samples. Controlling for patient age at diagnosis and tumor stage, Cox regression analysis showed that high cytolytic activity in tumor‐free samples associated with improved disease‐free survival (hazard ratio= 4.20, 95% CI = 1.09–16.20, p = 0.037). However, the degree of cytolytic activity in tumor samples did not provide prognostic information. Taken together, our results show the presence of cancer‐related immune responses in clinically tumor‐free tongue in patients with squamous cell carcinoma of the oral tongue. Measuring cytolytic activity in tumor‐free tongue samples contralateral to tumor might thus be an effective approach to predict clinical outcome.